Physiological Features of African Ostriches - Shakhlo, Babayeva; Ogabek, Begmurodov (European Journal of Life Safety and Stability (2660-9630), 2022)
This article examines the external features of African ostriches, the skills of their maintenance and the technology of cultivation in order to increase their productivity and achieve high economic efficiency in Uzbekistan - as used in many sectors of agriculture.